Literacy Champions: Lived Experiences of PhD Reading Scholars in the LiSQuP Program - Jeremiah Paul Manuel; Marnelli Bautista-Tolentino; Trixie Fabian Samson (Journal of Pedagogical and Teacher Professional Development, 2026)
This study was conducted to examine the lived experiences of the reading scholars in the LiSQuP program, engaging the stories of the scholars in their coursework. It utilized a phenomenological approach, capturing the authentic narratives of the participants, students of the reading program in the LiSQuP mechanism, and abstracting codes and themes from their responses. The findings of the study included four themes: LiSQuP’s Demanding Standards, Academic and Personal Milestones in the LiSQuP Scholar Experience, Advancing Core Literacy Skills through LiSQuP Scholarship, and Innovative Literacy Strategies and Leadership in Reading Education. This study contributes to the discussions in different fields and trends, opening channels of discussion and explorations in the areas of professional development, scholarship of teaching, reading specialization, literacy approaches, and studies on LiSQuP scholarship. This material provides different trajectories of research opportunities in these fields, culling in related disciplines in the construction of more knowledge.